Evaluation of Antibiotic Usage Using the Gyssens Qualitative Method in Pediatric Inpatients with Diarrhea at a Teaching Hospital in North Jakarta - Norman Dyanto; Diana Laila Ramatillah (Pelopor Publikasi Akademika, 2023)
Diarrhea is the second leading cause of death in children worldwide. Diarrhea is widespread in developing nations, Indonesia included. The primary treatment for diarrhea is the giving of rehydration fluids to prevent dehydration, and it generally does not require antibiotics. Giving antibiotics to pediatric patients with diarrhea indicates the presence of an infection, such as bloody diarrhea or cholera. Antibiotics are ineffective if not taken as prescribed and can lead to bacterial resistance. This study aims to understand the patient profile antibiotic usage, and evaluate the appropriateness of antibiotic use in pediatric inpatients with diarrhea using the Gyssens method at a Teaching Hospital in North Jakarta during the 2022 period. This research was a retrospective study that gathered data through qualitative analysis using the Gyssens algorithm to determine the appropriateness of antibiotic use in pediatric inpatients with childhood diarrhea at a Teaching Hospital in North Jakarta. The evaluation of antibiotic usage used the Gyssens flowchart, which included inclusion and exclusion criteria for assessing the appropriateness of antibiotic use. From this research, 81 patients are identified, with the majority of cases occurring in toddlers aged 0-5 years (86.4%), and the most common gender is male (58%). The most frequently prescribed antibiotic is ceftriaxone (40.6%), with the majority receiving only one antibiotic prescription (40.7%). The evaluation of antibiotics using the Gyssens method indicates that 45 patients (55.5%) are categorized as 0; 34 patients (42%) are categorized as IVa; and 2 patients (2.5%) are categorized as IIIa. No antibiotics categorized I, IIa, IIb, IIc, IIIb, IVb, IVc, or IVd. The evaluation of antibiotic usage using the Gyssens qualitative method for pediatric inpatients with diarrhea at a Teaching Hospital in North Jakarta during the 2022 period shows appropriate use.